Redox behavior of V/MgO catalyst in H2S wet oxidation at room temperature - Lee, EK; Jung, KD; Joo, OS; Shul, YG (SPRINGER, 2004)
The room temperature wet catalytic oxidation was conducted in a batch reactor with V/MgO catalyst. The XRD study of the catalyst used indicated that V/MgO could not only oxidize H2S to sulfur selectively, but also prevent the sulfidation of metal oxide effectively at room temperature. The XPS study indicated that the H2S oxidation with V/MgO could proceed by a redox mechanism (V5+ <----> V4+) and that V3+ formation (V4+--> V3+), was responsible for the deactivation of V/MgO.
Keywords: SELECTIVE OXIDATION; HYDROGEN-SULFIDE; OXIDE CATALYSTS; SULFUR